Regulation of electronic sports in Brazil: analysis of Bill 383/17 from the perspective of economic freedom (Revista Digital de Direito Administrativo, 2023)
The article analyzes the regulatory impact of the Senate Bill nº 383/17, which deals with the regulation of electronic sports in Brazil, from the perspective of economic freedom. The methodology used in the research was bibliographic, obtaining data for development based on books and articles. The work addresses the emerging market of electronic games in Brazil and in the world, identifying and differentiating the regulation of e-Sports in other countries. It also explores the Brazilian doctrine alluding to the ideals of free enterprise and the free market. Finally, the Bill nº 383/17 is analyzed and the relevance of its approval for the development of this market in the country is evaluated. The investigation demonstrates that the regulation of electronic sports in Brazil, seen from the perspective of economic freedom, should not occur in a way that unjustifiably limits the development of this activity, under penalty of violating the aforementioned principle, in addition to contradicting the dictates of the Declaration of Economic Freedom Rights (Act No. 13.874/2019).